2013
DOI: 10.2109/jcersj2.121.452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of P<sub>2</sub>O<sub>5</sub>/TeO<sub>2</sub> composition ratio on the physical properties of V<sub>2</sub>O<sub>5</sub>–P<sub>2</sub>O<sub>5</sub>–TeO<sub>2</sub> glasses for lead-free low-temperature sealing

Abstract: We examined how the composition ratio of P 2 O 5 to TeO 2 affected the physical properties and the structure of the semiconductive vanadate glasses in a low-melting V 2 O 5 P 2 O 5 TeO 2 glass system containing 57 mol % V 2 O 5 . It was found that increasing the P 2 O 5 content and correspondingly decreasing the TeO 2 content raised the glass transition temperature and the deformation temperature as well as the fraction of the reduced V ions ([V 4+ ]/[V total ]) and the average interionic distance of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…TeO 2 glasses can be classified into either Te‐rich glasses with around 50 mol% TeO 2 in binary and ternary systems with application in lasers, optical fibers, amplifiers, 1‐11 or into low‐Te glasses where TeO 2 is only added in low amounts as dopant 3,12‐15 . TeO 2 glasses are promising low phonon hosts for rare‐earth elements 1,16‐23 or present luminescence properties themselves 2 .…”
Section: Introductionmentioning
confidence: 99%
“…TeO 2 glasses can be classified into either Te‐rich glasses with around 50 mol% TeO 2 in binary and ternary systems with application in lasers, optical fibers, amplifiers, 1‐11 or into low‐Te glasses where TeO 2 is only added in low amounts as dopant 3,12‐15 . TeO 2 glasses are promising low phonon hosts for rare‐earth elements 1,16‐23 or present luminescence properties themselves 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The transparencies of glasses are noted, in contrast to the colored glasses having extremely low melting points, such as vanadium‐based glasses (V 2 O 5 –P 2 O 5 –TeO 2 ) and bismuth‐based glasses (Bi 2 O 3 –ZnO–B 2 O 3 –BaO). On the other hand, the enhanced T g and reduced amount of dissolution indicate that ZnO seems to play a role in the reinforcement of glass network structure, due to the incorporation of Zn 2+ as a network former into the B–O–B and P–O–P bonds.…”
Section: Resultsmentioning
confidence: 95%
“…Among the candidate compositions, V 2 O 5 -P 2 O 5 -based glasses have been studied a lot in order to overcome the narrow glass-forming area of vanadium-based glass. It was reported that, when P 2 O 5 is added into V 2 O 5 -based glass systems, the glass formation stability is improved [9,10]. However, there is a limit to its application as a sealing glass due to poor chemical durability and low water resistance [11].…”
Section: Introductionmentioning
confidence: 99%